Thermomechanical behaviour of composites with embedded metallic pins - Fu, yu; Neale, Geoffrey (Cranfield University, 2022)
MSc individual research project poster (2021-2022) modelling the thermomechanical behaviour of large metallic through-thickness reinforcing pins in compsosites presented by Yu Fu. Presents an the development and validation of a local thermomechnical model around the pin placed in the composite.
Keywords: 'Composite material'; 'Thermomechanical'; 'thermomechanical modeling'; 'Through-thickness reinforcement'